STRATEGI MENDAPATKAN PERMODALAN BAGI PELAKU USAHA MIKRO KECIL MENENGAH - Asmawiyah, Asmawiyah; Kapriani, Kapriani; Nurjaya, Nurjaya; Hariyanti, Hariyanti; Basar, Nur Fatwa; Agustuty, Lasty; Nurlinda, Nurlinda (Unit Publikasi dan Jurnal Sekolah Tinggi Ilmu Ekonomi Tri Dharma Nusantara Makassar, 2025)
Micro, Small, and Medium Enterprises (MSMEs) have a significant contribution to the national economy, but still face major obstacles in the form of limited access to capital that hinders business development. This study aims to examine strategies that can be implemented by MSME actors in obtaining financing sources that are appropriate to their needs and business capacity. The capital alternatives analyzed include formal financing such as bank loans and non-bank financial institutions, as well as informal financing through cooperatives, venture capital, and digital-based financial technology. The results of the study indicate that effective strategies in obtaining capital include increasing financial literacy, preparing measurable business plans, strengthening business management, and utilizing financial technology to expand access to funding. By implementing these strategies, MSMEs have the potential to increase competitiveness, expand markets, and contribute more optimally to national economic growth.